Digital twin product lifecycle system dedicated to the constant velocity joint. (July 2021) - Yujun, Lu; Zhichang, Zhao; Wei, Wang; Kui, Zhang
Highlights: l Integrate the multi-dimensional car constant velocity joint digital twin model through customized development of CATIA software. l Complete data transmission from sensor to digital twin through socket module. l Using ANSYS to carry out simulation test on car constant velocity joint. l Use algorithms to analyze the extracted vibration signals to predict the failure of the car constant velocity joint. Abstract: The constant velocity joint for the automobile is a key factor in realizing vehicle steering and propulsion, whose quality has a direct impact on the safety, maneuverability and comfort. To improve the manufacturing quality and later-stage maintenance efficiency of the constant velocity joint, a multi-dimensional digital twin model dedicated to product lifecycle of the constant velocity joint is established in this paper. Combing with the actual manufacturing process and process of the constant velocity joint, the three-dimensional(3D) modeling of its parts is established. Using computer simulation technology to reduce its production and test costs, so that the digital twin model has the ability to diagnose faults and optimize design. Using algorithm analysis and experience evaluation to process real-time data to achieve the purpose of predictive maintenance of constant velocity joint. The customized software based on CATIA is developed, and the digital twin model dedicated to product lifecycle of the constant velocity joint is verified which realize the balance between product standardization and manufacturing flexibility. Graphical abstract: Image, graphical abstract